2020
DOI: 10.1042/bsr20194335
|View full text |Cite
|
Sign up to set email alerts
|

SKA3 promotes lung adenocarcinoma metastasis through the EGFR–PI3K–Akt axis

Abstract: The processes that lead to lung adenocarcinoma (LUAD) metastasis are poorly characterized. Spindle and kinetochore associated complex subunit 3 (SKA3) plays a key role in cervical cancer development, but its contribution to LUAD is unknown. Here, we found that SKA3 is overexpressed in LUAD and its expression correlates with lymph node metastasis and poor prognosis. SKA3 silencing experiments identified SKA3 as an oncogene that promotes the metastasis of LUAD cell lines and tissues. SKA3 was found to induce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 32 publications
1
38
1
Order By: Relevance
“…However, according to our results, SKA3 proteins in uenced the progression of HCC and PAAD tumors. Therefore, we speculated that SKA3 could have different biological functions in both tumors, an observation that is contrary to previous studies [22,27].…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…However, according to our results, SKA3 proteins in uenced the progression of HCC and PAAD tumors. Therefore, we speculated that SKA3 could have different biological functions in both tumors, an observation that is contrary to previous studies [22,27].…”
Section: Discussioncontrasting
confidence: 87%
“…SKA3 is one of the important cyclins. Although some studies have suggested that SKA3 could in uence the progression of certain cancers [22,23], the mechanism underlying its role is still largely unclear and controversial [24][25][26]. Herein, we explored the relationship between SKA3 and the diagnosis and prognosis of HCC and PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…As an important component of the spindle and kinetochore-related complexes 29 , SKA3 is essential for regulating mitosis with NDC80 complex and thus controlling cell proliferation and apoptosis 26 , 30 . Aberrant expression of SKA3 is closely associated with tumorigenesis and development 14 , 30 . For instance, SKA3 binds EGFR and consequently activates PI3K–AKT, thus promoting lung adenocarcinoma metastasis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of SKA3 is closely associated with tumorigenesis and development 14 , 30 . For instance, SKA3 binds EGFR and consequently activates PI3K–AKT, thus promoting lung adenocarcinoma metastasis 14 . However, although EGFR mutation is rare in LSCC, SKA3-mediated AKT activation mainly depends on the serine/threonine-protein kinase PLK1 as silencing of PLK1 significantly attenuated the increase in p-AKT caused by SKA3 overexpression (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation